An Approach to Wideband and High Accuracy Microwave Photonic Signal Carrier Recovery Based on Carrier Period Measurement - Qingming Zhu; Ruiyuan Cao; Shaohua An; Yikai Su; Jianping Yao (IEEE Photonics Journal)
We propose and experimentally demonstrate an approach to carrier frequency and phase recovery of a microwave photonic signal based on carrier period measurement (CPM). In the approach, a coarse carrier frequency offset (CFO) estimation is first performed, which is realized by measuring the crossing period of the microwave signal with its mean level. Then, an envelope detection method is used to simultaneously estimate the residual CFO and the carrier phase. Through the two steps, wideband and high-accuracy carrier recovery can be realized. The proposed approach is validated by an experiment. Effective carrier recovery of a microwave photonic signal is achieved with a carrier frequency varying from 7 to 37 GHz carrying a 2-Gbaud on–off-keying or quadrature phase shift keying baseband signal. The CFO estimation range is from −21 to +9 GHz, and the CFO estimation errors are less than 0.1 MHz.